Carbonate system buffering in the water masses of the Southwest Atlantic sector of the Southern Ocean during February-March 2008 - González-Dávila, Melchor; Santana-Casiano, J. Magdalena; Fine, R. A.; Happell, J.; Delille, B.; Speich, S. (2013)
Carbonate system variables were measured in the South Atlantic sector of the Southern Ocean along a transect from South Africa to the southern limit of the Antarctic Circumpolar Current (ACC) in February-March 2008. Eddies detach from retroflection 5 of the Agulhas Current located north of the Subantarctic Front (SAF). The eddies increase the gradients observed at the fronts so that minima in f CO2 and maxima in pH in situ on either side of the frontal zone are observed, while within the frontal zone f CO2 reached maximum values and pH in situ was a minimum. Mixing at the frontal zones, in particular where cyclonic rings were located, brought up CO2 -rich water (low pH and 10 high nutrient) that spread out the fronts where recent biological production favored by the nutrient input increases the pH in situ and decreases the f CO2 levels. Vertical distributions of water masses were described by their carbonate system properties and their relationship to CFC concentrations. Upper Circumpolar Deep Water (UCDW) and Lower Circumpolar Deep Water (LCDW) had pHT,25 values of 7.56 and 7.61, respectively. UCDW also had higher concentrations of CFC-12 (>0.2 pmol kg−1 15 ) as compared to deeper waters, revealing the mixing with recently ventilated waters. Calcite and aragonite saturation states (Ω) were also affected by the presence of these two water masses with high carbonate concentration. Ωarag = 1 was observed at 1000 m in the subtropical area and north of the SAF. At the position of the Polar front 20 and under the influence of UCDW and LCDW Ωarag = 1 deepen from 600 m to 1500 m at 50.37◦ S, and it reaches to 700 m south of 57.5◦ S. High latitudes are the most sensitive areas under future anthropogenic carbon increase. Buffer coefficients related to changes in [CO2 ], [H+ ] and Ω with changes in CT and AT showed the minimum values are found in the Antarctic Intermediate Water (AAIW), and UCDW layers. These 25 coefficients suggest that a small increase in CT will sharply decrease the pH and the carbonate saturation states. Here we present data that are used to suggest that south of 55◦ S by the year 2045 surface water will be undersaturated in aragonite.